Synchrotron Radiation and ALBA Facility - García-Aranda, Miguel Ángel (My University, 2017)
ALBA synchrotron light source (www.cells.es) is the largest Spanish research infrastructure that started full operation of its first 7 beamlines on February 2013. I will divide the talk in three parts: i) the general description of the facility; ii) the eight beamlines currently operating at ALBA; and iii) the three beamlines which are under design/construction. I will start with a very brief description of the facility including the construction costs, staff structure and general parameters. Then, I will briefly describe our three accelerators: LINAC, booster and the store ring. Some characteristic parameters will be described. To finish this part, I will touch the three main magnetic technologies to produce X-rays from the ALBA electron beam. Secondly, I will concisely describe the eight beamlines with their main application fields. A photography of our experimental hall with a Table displaying the current beamlines is shown just below. The ways to use ALBA including the call-for-proposals will be described. The proposals (both national and internationals) are judged by an international panel on the basis of scientific excellence. Finally, I will briefly explain the current construction stage of the new beamlines.
Keywords: Cristalografía por rayos X; sincrotrón; ALBA; beamlines; CELLs-ALBA